Perlindungan Pekerja dalam Kemitraan Semu: Analisis Putusan Nomor 191/Pdt.Sus-PHI/2023/PN Jkt.Pst - Andi Harsayudi; FX Suyud Margono; Bahori Ahoen (Social Science Academic, 2026)
The rapid evolution of modern business models has led to the widespread adoption of partnership schemes, which frequently obscure genuine employment relationships (disguised employment relationships). This study aims to analyze in depth the legal implications of establishing employment status on the fulfillment of workers' normative rights and to evaluate the judges' legal reasoning (ratio decidendi) in the Industrial Relations Court Decision at the Central Jakarta District Court Number 191/Pdt.Sus-PHI/2023/PN Jkt.Pst. Utilizing normative legal research with statutory, conceptual, and case approaches, this study examines the fulfillment of employment elements under Law No. 13 of 2003 jo. Law No. 6 of 2023, comparing them with Supreme Court jurisprudence and accredited scientific literature. The findings reveal that the determination of employment status serves as a constitutive entry point for enforcing normative rights, social security guarantees, and protection against unilateral termination. Furthermore, the judge's ratio decidendi aligns with Gustav Radbruch's Formula by prioritizing the substance over form doctrine, the Control Test, and the Economic Dependency Test. Operational control, trip-based wage compensation, and economic dependency supersede formal partnership labels, thereby securing substantive justice, fair legal certainty, and social utility in industrial relations.